Respon Penambahan Asam Humat terhadap beberapa Kandungan Senyawa Aktif Pegagan (Centella asiatica) - triani hardiyati; Elly Proklamasiningsih; Iman Budisantoso (Fakultas Biologi Universitas Jenderal Soedirman, 2020)
The aim of this research is to know the respon of humic acid and some growth media on the contain of active biological substance in Centella asiatica (L.) Urb. Hopefully, through the application of humic acid in the combination of media, the growth and plant metabolism will improve to produce active biological substance as primar metabolism. The growth media used were : soil & sand (1 : 1) ; soil & husk (1 : 1 ) ; and soil & zeolite (1 : 2). The humic acid treatment were 4 concentration, 0 g/kg media, 4 g/kg media, 8 g/kg media and 12 g/kg media. The research method was Completely Randomized Design, with factorial as treatment design. The variable observed were alkaloid content, flavonoid content, the presence of terpenoid, and biomass weight. The research result showed that the high weight of biomass and alkaloid contain got in the addition of 8 g humic acid in media soil and sand. The high flavonoid contain got in addition of 4 g/kg media in media soil and zeolite. There was brawn ring in the extract analysis dissolved in chloroform, acetic acid, and strong sulfate acid.